2007
DOI: 10.1074/mcp.m600439-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale Identification of Proteins, Mucins, and Their O-Glycosylation in the Endocervical Mucus during the Menstrual Cycle

Abstract: The mucus filling the human cervical opening blocks the entry to the uterus, but this has to be relative and allow for the sperm to penetrate at ovulation. We studied this mucus, its content of proteins and mucins, and the mucin O-glycosylation in cervical secretions before, during, and after ovulation. Cervical mucosal secretions from 12 subjects were collected, reduced-alkylated, separated with polyacrylamide or agarose/polyacrylamide gel electrophoresis, and stained with silver, Alcian blue, or Coomassie Bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
156
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(173 citation statements)
references
References 34 publications
(35 reference statements)
13
156
2
1
Order By: Relevance
“…Vaginal 3-D aggregates expressed a lower percentage of MUC1 (27.7%) compared to monolayers (67.2%). The lower percentage of MUC1 on the 3-D aggregates surface compared to monolayers may be a result of the majority of MUC1 being secreted from the cells as observed in the vaginal tract 17,18 .…”
Section: Representative Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Vaginal 3-D aggregates expressed a lower percentage of MUC1 (27.7%) compared to monolayers (67.2%). The lower percentage of MUC1 on the 3-D aggregates surface compared to monolayers may be a result of the majority of MUC1 being secreted from the cells as observed in the vaginal tract 17,18 .…”
Section: Representative Resultsmentioning
confidence: 99%
“…We and others have shown that RWV-derived models utilizing human cells may be a valuable tool for predicting the efficacy, toxicity and pharmacokinetics of vaccines, microbicides, biologics and pharmaceuticals in a fashion that is relevant to humans 1,2,18 . With the success of this bioreactor culture system to produce authentic human responses, combined with its flexibility, the applications of the RWV bioreactor system is currently being expanded to such fields as tumor modeling, regenerative medicine, and tissue engineering 2,[18][19][20][21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the challenge of discovering MUC16/CA125 structure necessitates integrated and cooperative efforts. Recent studies have been undertaken by investigators who have focused on analysis of this biomarker from different biological sources by proteomic approaches using the MALDI-TOF mass spectrometry [70,72], the tandem mass spectrometry [MS/MS] [68,73] or the nano-LC-FT-ICR MS [74,75]. Although mucins are difficult to identify with proteomics as most of their peptides are glycosylated and thus not identified in the protein databases [72], implementation of such approaches is likely to yield more information about the complexity of MUC16/CA125 and to achieve a substantial depth of analysis.…”
Section: After More Than 20-years Effort To Characterize the Antigen mentioning
confidence: 99%